Risk Analysis in Facing the Production of Laying Hens (Case Study in Ringinsari Village, Kandat District, Kediri Regency) - Dona Wahyuning Laily; Ida Syamsu Roidah; Fatchur Rozci; Ika Purnamasari (Nusantara Science and Technology Proceedings, 2023)
Laying chickens are a commodity that is popular with the public for fulfillment of animal protein requirements. In cultivating laying hens, several risks must be taken into account. This research aims to analyze sources of risks faced, priority risk levels and management strategies risks of the laying hen farming business carried out by laying hen breeders in The research location is Ringinrejo Village, Kandat District, Kediri Regency. Respondents to the research were 62 breeders using the census method of laying hens. In analyzing risk sources, the Fishbone Diagram is used. In analyzing the risk level, qualitative descriptive analysis of management strategies farm management. From the research results, there are two sources of risk, namely production risk and price risk. The highest production risk is characterized by the presence of climate warming, disease attacks, weather changes, limited capital, poor feed quantity and quality, as well as pest attacks. While at-risk prices were marked by a decrease in egg prices and an increase in feed prices. Therefore, breeders can explain several strategies, namely by expanding distribution channels and establishing cooperation, developing cages adaptive, preventing and treat pests and diseases, as well as Improving the quality of human resources.